The Level of Importance of Criteria and Sub Criteria in Green Building Index Malaysia - Rahardjati, Retno; Khamidi, M. Faris; Idrus, Arazi (2010)
The aim of this paper is to determine the level of importance of criteria and sub criteria in Green Building Index Malaysia (GBIM) for nonresidential building. Green building rating system (GBRS) provides a framework for assessing building environmental performance into green building. Several GBRS are in use today and being developed at all levels. In May 2009, GBIM was launched to evaluate building performance and awards rating through six criteria. However, there should be improvement in technical services and resources for determining how friendly the building environmentally based on the proper GBRS that suits Malaysia local context so implementation is easier. Therefore, this paper takes a pair-wise comparison method using Analytical Hierarchy Process (AHP). In AHP, each comparison is scaled from equally to extreme importance by the number of 1 to 9 and weighted to meet the level of importance. Survey questionnaires were distributed to define the weighting of criteria and sub criteria based on respecting local conditions of Malaysia. The findings show that the current GBIM and survey result are different in their level of importance of criteria and sub criteria.